Synthesis and evaluation of the anti-hepatitis B virus activity of 4′-Azido-thymidine analogs and 4′-Azido-2′-deoxy-5-methylcytidine analogs: structural insights for the development of a novel anti-HBV agent. (2nd April 2020) - Onitsuka, Kengo; Tokuda, Ryoh; Kuwata-Higashi, Nobuyo; Kumamoto, Hiroki; Aoki, Manabu; Amano, Masayuki; Kohgo, Satoru; Das, Debananda; Haraguchi, Kazuhiro; Mitsuya, Hiroaki; Imoto, Shuhei
Abstract: Hepatitis B virus (HBV) infection is a major worldwide health problem that requires the development of improved antiviral therapies. Here, a series of 4′-Azido-thymidine/4′-Azido-2′-deoxy-5-methylcytidine derivatives (6, 10–15 ) were synthesized, and their anti-HBV activities evaluated. Compounds 10–15 were synthesized via an SN Ar reaction of 18, in which the 4-position of the thymine moiety was activated as the 2, 4, 6-triisopropylbenzenesulfonate. Compounds 11–15 showed no antiviral activity. However, 4′-Azido thymidine (6 ) and 4′-Azido-2′-deoxy-5-methylcytidine (10 ) displayed significant anti-HBV activity (EC50 = 0.63 and 5.99 µ M, respectively) with no detectable cytotoxicity against MT-2 cells up to 100 µ M.